THE NAHDLATUL ULAMA: Its Early History and Contribution to the Establishment of Indonesian State (State Islamic University (UIN) of Sunan Ampel Surabaya, 2011)
Established on 31 January 1926 in Surabaya, East Java, by some prominent kyais like K.H. Abdul Wahab Hasbullah and K.H. Hasyim Asy’ari, the Nahdlatul Ulama was born in the culture of pesantren where ‘traditional Islam’ has been rooted and preserved. In this context, the Nahdlatul Ulama declared its religious ideology as ‘ahl al-sunnah wa al-jama’ah.’ This religious ideology has become important characteristics of the Nahdlatul Ulama that differentiate itself from Muslim ‘modernist’ organizations. In its early movements, the Nahdlatul Ulama plyed a pivotal role by, for example, banning the Muslim youths from entering the Dutch military service, prohibiting the Muslims from supporting the Dutch army, and rejecting the Dutch aid which was offered to the Nahdlatul Ulama’s madrasas. Furthermore, together with other nationalist movements, the Nahdlatul Ulama actively took part in the process of establishing the Indonesian State and in the war to defend the Indonesian independence against the Dutch who tried to re-establish their colonial rule in Indonesia. These facts, undoubtedly, proved that the Nahdlatul Ulama made a great contribution to the nation and state of Indonesia.